PENINGKATAN KEMAMPUAN MOTORIK KASAR ANAK USIA DINI KELOMPOK B MELALUI PERMAINAN TRADISIONAL LOMPAT TALI - Rindawati Rindawati; Devi Wahyu Ertanti; Ika Anggraheni (UNISMA, 2022)
Mobile phones or gadgets that are idols for today's children are like a coin with two sides, namely positive and negative sides. The widespread use of gadgets is the waning of traditional games for children, especially for early childhood. The most interesting and different traditional game at RA Sunan Kalijogo is the jump rope game, the jump rope game is a modified traditional game that is still preserved. This type of research is a qualitative research with a case study approach. The result of the research is that the traditional jumping rope game is carried out in stages, according to the theme and is effective for improving children's fine motor skills